Influence of Knowledge Transfer Methods on Librarians’ Attitude Towards Cataloguing and Classification in University Libraries in South-West, Nigeria - Umahi, Felicia O.; Madukoma, Ezinwanyi; Unegbu, Vincent E. (Communicate: Journal of Library and Information Science, 2025)
This study investigated the influence of knowledge transfer methods on librarians’ attitude towards cataloguing and classification in university libraries in South-West, Nigeria. The study adopted a survey research design. The population comprised 403 librarians from 54 university libraries in South-West, Nigeria. Total enumeration was used. Self-structured and validated questionnaire was used for collection of data. Cronbach’s alpha reliability coefficients for the constructs ranged from 0.74 to 0.96. A response rate of 78.9% was achieved. Data were analyzed using descriptive and inferential statistics at 5% significance level. Findings revealed that knowledge transfer methods significantly influenced librarians’ attitude towards cataloguing and classification in university libraries in South-West, Nigeria (R2 = 0.20, β= 0.45, t(316) = 8.88, p < 0.05). Further analysis showed that on-the-job training (β = 0.217, t(314) = 3.48, p < 0.05) and off-the-job training (β = 0.337, t(314) = 5.79, p < 0.05) had positive influence, while lecture methods (β = 0.04, t(314) = 0.63, p > 0.05) had no influence on librarians’ attitude towards cataloguing and classification. In conclusion, knowledge transfer methods enhanced librarians’ attitude positively towards cataloguing and classification, in university libraries in South-West, Nigeria. Therefore the study recommended that the university management should formulate and implement policies and incentives that can support mentorship, sponsorship for training and re-training of librarians in cataloguing and classification in order to change this negative attitude.